Prediction of disease progression and treatment success: Importance of individualized treatment approaches Prädiktion von Krankheitsverlauf und Therapieerfolg: Stellenwert individualisierter Therapieansätze - Atreya, Raja (Die Gastroenterologie, 2023)
Background: Although the introduction of targeted therapies has led to a significant improvement in the care of patients with inflammatory bowel diseases (IBD), only a subgroup of the treated patients benefit from the initiated treatments. Furthermore, the individual disease course in patients with IBD is often unclear. Objectives: To what extent are currently available predictive biomarkers able to predict treatment response and disease progression in IBD patients? Materials and methods: Evaluation of available studies that have characterized potential biomarkers to evaluate treatment response and disease progression. Results: Substantial progress has been made in various areas of biomarker studies to identify relevant biomarkers, yet their use in clinical practice is still not foreseeable. Conclusion: Potential biomarkers must be validated in independent cohorts with comparable endpoints before they can be used in daily clinical practice.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Biologicals; Biomarkers; Infliximab; Precision medicine; Therapy resistance